The Comparison of the Effect of Two Methods of Self-Modelling and Video Demonstration of an Expert on the Acquisition and Retention of Volleyball Serve Skill - Rasoul Suzande pour; Ahmad Reza Movahedi; Leila Mazaheri; Gholamreza Sharifi (University of Tehran, 2009)
The purpose of the present study was to compare the effects of two methods of self-modeling and video demonstration of an expert on the acquisition and retention of volleyball serve skill. Participants were 30 students (aged between 12 and 14) who were assigned into two homogeneous groups after the pretest. The self-modeling group (n = 15) watched their performances in the criterion task via a video while the expert demonstration group (n = 15) observed the performance of an expert in the criterion task via a video. Both groups received the verbal cues and instructions. The two groups exercised the task for 4 weeks, 3 sessions per week. Immediately after the 12th session of exercise, a posttest, and 10 days later, a retention test was taken. Paired and independents t test were used to analyze the data. Results showed that both groups improved their performances significantly in acquisition and retention tests. No significant difference was found between the two groups in the acquisition of the skill but the expert demonstration group significantly improved their serve skill in the retention test. It seems that video demonstration of an expert improves students' learning of volleyball serve skill.